2006
DOI: 10.1590/s0103-63512006000300002
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of advertising intensity in the Brazilian manufacturing industry: an econometric study

Abstract: The paper econometrically investigates the determinants of advertising intensity in the manufacturing industry of São Paulo, Brazil in 1996 taking as reference an extensive survey carried out by Fundação SEADE. The preliminary investigation indicated a substantial degree of endogeneity in structure and performance variables. The instrumental variables estimation also considered instruments referring to information technology and organizational practices and indicated relevant roles for industrial concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Given the extended lifespan of durable goods and their inherent complexity, consumers will conduct more comprehensive searches of the available products, carefully assessing their distinct characteristics and attributes. 2 Due to the generally higher prices of such goods, any errors in evaluating them would lead to greater consumer welfare losses (Resende, 2006). When buying durable products, consumers may consult unbiased sources like specialist magazines to acquire information rather than relying solely on the seller's advertising, which, besides being informative, also has a persuasive purpose (Jones, 2004).…”
Section: 𝑃𝑃𝐶𝐶: Concentration Ratio (The Four-firm Concentration Ratio)mentioning
confidence: 99%
“…Given the extended lifespan of durable goods and their inherent complexity, consumers will conduct more comprehensive searches of the available products, carefully assessing their distinct characteristics and attributes. 2 Due to the generally higher prices of such goods, any errors in evaluating them would lead to greater consumer welfare losses (Resende, 2006). When buying durable products, consumers may consult unbiased sources like specialist magazines to acquire information rather than relying solely on the seller's advertising, which, besides being informative, also has a persuasive purpose (Jones, 2004).…”
Section: 𝑃𝑃𝐶𝐶: Concentration Ratio (The Four-firm Concentration Ratio)mentioning
confidence: 99%
“…In addition, Misra showed that advertising intensity is relatively higher in consumer goods industries compared to producer goods industries. Resende (2006) used 2SLS regression technique because he believed that in case of simultaneous causal relationships between the variables, simple regression would fail to provide an accurate result. Of course, unlike Resende, several other researchers have disregarded this possibility as an accuracy threat (Willis, 1998;Strickland and Weiss, 1976, etc.).…”
Section: Journal Of Management Researchmentioning
confidence: 99%